Lieuxpatrimoniaux.ca - Welcome to / Bienvenue à HistoricPlaces.ca / LieuxPatrimoniaux.ca
https://nationaltrustcanada.ca/online-stories/alarm-as-canadian-register-of-historic-places-to-shut-down
Keywords: _open access

Residential Schools Locations Project
This dataverse contains datasets associated with the Residential Schools Locations Project. This datasets in this project show the precise locations of the Residential Schools (Boarding Schools, Industrial Schools and Hostels) in Nova Scotia, Quebec, Ontario, Manitoba, Saskatchewan, Alberta, British Columbia, Yukon Territory, Northwest Territories and Nunavut. Data was created by Rosa Orlandini with significant contributions from the National Centre for Truth and Reconciliation, and minor contributions from Morgan Hite and Stephanie Pyne.
Keywords: _open access

Historical Atlas of Canada Online Learning Project
Data for maps from the Historical Atlas of Canada Online Learning Project (HACOLP), preserved here largely for preservation purposes. HACOLP was a series of interactive online maps based on maps in the published Historical Atlas of Canada series. Data deposited by Byron Modolfsky, cartographer for the Historical Atlas of Canada, summer 2019.
Keywords: _open access

The Canadian Peoples 1871-1921 census data
The Canadian Peoples (TCP) data infrastructure encompasses 40 million coded and georeferenced census records from 1852-1921 including personal, family and household characteristics for every individual in each enumeration. The Canadian Foundation for Innovation, provincial research funds in Quebec, Ontario and Alberta, nine Canadian universities and Ancestry.com have funded the project. The owner of these data, Ancestry.com, has agreed to license their use for academic research and educational purposes only, with no right to publish, transfer, share, sub-license or distribute any portion of the data. Access to data for research and educational purposes may occur upon approval of a completed application by the TCP approvals committee. Any research institution or research seeking access to any of the data within this collection will need to complete the application form and send it to the TCP project director Kris Inwood at: kinwood@uoguelph.ca The first census year for distribution is 1871; the data for other years will follow as soon as they can be made ready.
Keywords: _open access

Rapports de Parcs Canada
Portail de publications électroniques sur l’histoire culturelle et naturelle du réseau des parcs nationaux du Canada, qui inclut comprend 48 parcs nationaux / réserves, un parc urbain national, 1,007 lieux historiques nationaux (dont 171 sont administrés par Parcs Canada, y compris neuf canaux du patrimoine), quatre aires marines de conservation nationales, un point de repère national, ainsi que des documents de l'histoire de l'agence chargée de gérer ce système: Parcs Canada.
Keywords: _open access

Royal Ontario Museum
Collections consacrées à l’art, à la nature et aux cultures du monde entier et de toutes les époques
Keywords: _open access

Ingenium (Musée des sciences de l’innovation du Canada)
Ingenium – Le Musée des sciences de l’innovation du Canada à Ottawa crée des expositions hors concours, des programmes accessibles et adaptés aux familles ainsi que des recherches collaboratives qui prennent vie grâce à notre collection nationale d’artefacts.
Keywords: _open access

The New Montreal gazette 1834 - Canadianaorg (Printed and Published by Robert Weir, Junior, 1834)
Keywords: _open access

Recherche d'une mention dans le répertoire des actes d'état civil (baptêmes, mariages, sépultures) 1621-1861 (PRDH-IGD, Programme de recherche en démographie historique - Institut généalogique Drouin)
Keywords: _open access

36 volumes of the Irish University Press Series of British Parliamentary Papers (Canadiana)
These volumes, comprising the “Colonies, Canada” and “Colonies, Canadian boundary” series, were selected based on their relevance to Canadian history, and cover topics related to Great Britain’s administration of Canada from 1802-1899. Digitization was completed by CRKN from volumes held at the University of Alberta Library, with one additional volume generously lent by the University of Ottawa Library. The Irish University Press Series of British Parliamentary Papers was published between 1968-71 and comprises 1,000 volumes in total. The University of Alberta Library is one of the few known institutions to hold the entire collection, which contains invaluable information about British colonization and the administration of the British Empire in the 19th century. The “Colonies: Canada” and “Colonies: Canadian Boundary” volumes from the collection are regularly used by researchers and faculty at the University of Alberta, and will now be available to researchers globally through their availability on Canadiana.
Keywords: _open access

CUBIQ - Gouvernement du Québec
CUBIQ (catalogue unifié des bibliothèques gouvernementales du Québec) est le catalogue collectif des bibliothèques du RIBG. Il permet de repérer sur Internet les publications disponibles dans les bibliothèques des ministères et organismes du gouvernement du Québec qui utilisent les services du RIBG pour gérer leurs opérations. Sa mise à jour est quotidienne. CUBIQ renferme une collection vaste et diversifiée de : 500 000 livres; 250 000 publications gouvernementales; 14 000 revues et journaux. CUBIQ permet de consulter à l’écran un nombre grandissant de publications. Actuellement, plus de 100 000 titres sont disponibles en ligne.
Keywords: _open access

L'action nationale (BAnQ)
1933-...
Keywords: _open access

La Revue moderne (BAnQ)
1919-1960
Keywords: _open access

La Revue Populaire (Canadiana)
1907-1920
Keywords: _open access

Revue canadienne (Canadiana)
1864-1920
Keywords: _open access

The Canadian magazine (Canadiana)
1893-1921
Keywords: _open access

Canada Census Search - Library and Archives Canada
Application Description
Last Modified: Date modified (YYYY-MM-DD) / Date de modification (AAAA-MM-JJ)
Keywords: _open access

Canadian Statistical Review - Statistics Canada
Keywords: _open access

Historical Statistics of Canada - ARCHIVED - Statistics Canada
The second edition of Historical statistics of Canada was jointly produced by the Social Science Federation of Canada and Statistics Canada in 1983. This volume contains about 1,088 statistical tables on the social, economic and institutional conditions of Canada from the start of Confederation in 1867 to the mid-1970s. The tables are arranged in sections with an introduction
Keywords: _open access

Canada Year Book (CYB) Historical Collection - Statistics Canada (2008)
Coverage: 1867 - present
Last Modified: 2008-03-31
Keywords: _open access

POLTEXT - Données textuelles pour l'analyse des politiques du Canada - U Laval
Keywords: _open access

Labour Gazette - Internet Archive
Early issues edited by then labour minister, William Lyon Mackenzie King. Provides statistics on workers, the work they did, wages, the industries, and more. Coverage: 1900 - 1978
Keywords: _open access

Indian Affairs Annual Reports, 1864-1990 - Canada, Library and Archives (2022)
This database includes annual reports from the Department of Indian Affairs and Northern Development and its predecessors from 1864 to 1990. The reports in this database have been digitized, transcribed, and can be viewed online.
Last Modified: 2023-01-11
Keywords: _open access

Documents relatifs aux relations extérieures du Canada /Documents on Canadian external relations - Ministère des affaires extérieures Canada
1908-1963
Keywords: _open access

Publications gouvernementales - Canadiana
Find publications on a broad range of topics relating to indigenous rights, labour, justice, arts and literature, and the military.
Keywords: _open access

Ressources parlementaires historiques canadiennes - Bibliothèque du Parlement
Base de données qui contient les versions numérisées des publications parlementaires depuis la 1re session de la 1re législature (1867) jusqu’au début de leur diffusion sur noscommunes.ca et sencanada.ca.
Keywords: _open access

Parlinfo - Parlement du Canada
de 1867 à nos jours. People, Parliament, Departments and Committees, Political Parties, Legislation, Elections and Ridings.
Keywords: _open access

British Columbia Historical Newspapers - UBC
Keywords: _open access

Archeion - Archives Association of Ontario
archives held by organizations all over Ontario
Keywords: _open access

The Black Press
Keywords: _open access

Early Americas Digital Archive
A collection of electronic texts originally written in or about the Americas from 1492 to approximately 1820.
Keywords: _open access

Canadian Pamphlets and Broadsides - Thomas Fisher Rare Book Library
This collection provides access to the pre-1930 Canadian pamphlet and broadside holdings of the Thomas Fisher Rare Book Library by supplying both page images in full colour, and full searchability of the contents of each item. To date the site consists of 597 broadsides (single sheets, printed on one or both sides) and 2,062 pamphlet titles which amounts to 71,508 page images. The collection includes items printed in Canada, by Canadian authors, or about Canadian subjects, mainly of a non-literary nature.
Keywords: _open access

Archives Révolutionnaires
«Projet collectif en activité depuis 2017... intérêt particulier pour les luttes d’émancipation populaires, décoloniales, anti-impérialistes, féministes, LGBTQ+ ou antiracistes dans un horizon communiste et autogestionnaire.»
Keywords: _open access

Affiches de guerre - Calypso
La collection d’affiches de guerre des bibliothèques de l’Université de Montréal se compose de plus de 3000 images produites au cours des deux guerres mondiales ainsi que de l’entre-deux-guerres. Chaque affiche a été numérisée et son contenu a fait l’objet d’une description détaillée.
Keywords: _open access

The Fur Trade in Canada - La traite des fourrures au Canada
Site de recherche universitaire illustrant l'âge épique de la traite des fourrures au Canada en retraçant les hauts faits de la Compagnie du Nord-Ouest et d'autres entreprises de traite de Montréal à la fin du XVIIIe et au début du XIXe siècle
Keywords: _open access

Dossier France-Amérique - BNF; Library of Congress
Le site explore l'histoire de la présence française en Amérique du Nord depuis les premières décennies du XVIe siècle jusqu'à la fin du XIXe siècle
Keywords: _open access

Famili@ - Base documentaire des recherches sur les familles du Québec
Depuis mai 1998, Famili@, base documentaires francophone, diffuse un contenu scientifique multidisciplinaire concernant la recherche sur la famille au Québec. À ce jour, plus de 15 000 résumés!
Keywords: _open access

Canadian War Poster Collection - Rare Books & Special Collections, McGill Library
Keywords: _open access

Répertoire du patrimoine culturel du Québec
Keywords: _open access

Musée McCord Stewart
les archives portent sur l’ensemble de l’histoire canadienne, mais plus particulièrement sur celle de Montréal et des Montréalais au cours des 19e et 20e siècles.
Keywords: _open access

Musée de la civilisation (Collections - Musée de la civilisation)
Plus d’un quart de million d’objets. More than a quarter of a million objects.
Keywords: _open access

Musée canadien de l'histoire
Ancien Musée canadien des civilisations, et avant cela Musée national de l’Homme
Keywords: _open access

Les archives du Monastère des Augustines
Les archives des Augustines permettent de retracer l’évolution des soins de santé, du développement social, de la vie en communauté et de l’établissement de douze hôpitaux au Québec depuis les premiers temps de la colonie.
Keywords: _open access

Canadian Cultural History About The Spanish Civil War
Keywords: _open access

BAnQ numérique
Partez à la découverte de BAnQ numérique. 1524 - 1970s. French and English language periodicals from Quebec.
Keywords: _open access

Artefacts Canada - Gouvernement du Canada, Ministère du Patrimoine canadien
Artefacts Canada propose un accès à de l'information sur des millions d'objets de musées, fournis par des musées et des organismes patrimoniaux de partout au Canada.
Last Modified: 2006-08-24
Keywords: _open access

Advitam (Advitam)
La nouvelle interface des Archives nationales
Keywords: _open access

SFU Digitized Newspapers
contient entre autres des journaux de communautés immigrantes.
Keywords: _open access

Democracy at War: Canadian Newspapers and the Second World War | La Démocratie en guerre : Les journaux canadiens et la Seconde Guerre mondiale
Musée canadien de la guerre : La démocratie en guerre : les journaux canadiens et la Seconde Guerre mondiale : contient plus de 140 000 coupures de presse, organisées par sujet et par date, regroupe des articles et des éditoriaux de journaux, pour la plupart canadiens, qui couvrent tous les aspects de la guerre.
Keywords: _open access

Les journaux canadiens-français : une ressource historique essentielle (1808-1919)
contient des journaux canadiens parus en français partout au Canada.
Keywords: _open access

Collection historique de l'Annuaire du Canada (AC) - Gouvernement du Canada, Statistique Canada
La Collection historique de l'Annuaire du Canada couvre le premier siècle de l'histoire du Canada - plus précisément la période entre 1867 et 1967 - avec des textes historiques, cartes, tableaux et graphiques, auxquels s'ajoutent des ressources d'apprentissage interconnectées destinées aux étudiants et aux enseignants.
Last Modified: 2008-03-31
Keywords: _open access

Débats parlementaires Québec
voir la section « Débats parlementaires » du guide
Keywords: _open access

Ad*Access / Digital Collections / Duke Digital Repository (Duke Digital Collections)
Over 7,000 U.S. and Canadian advertisements covering five product categories - Beauty and Hygiene, Radio, Television, Transportation, and World War II propaganda - dated between 1911 and 1955.
Keywords: _open access